2016
DOI: 10.1186/s13578-016-0102-x
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous H2S modulates mitochondrial fusion–fission to inhibit vascular smooth muscle cell proliferation in a hyperglycemic state

Abstract: AimVascular smooth muscle cell (VSMC) proliferation in response to hyperglycemia is an important process in the development of arterial vessel hyperplasia. The shape change of mitochondria is dynamic and closely related to fission and fusion. Hydrogen sulfide (H2S) was confirmed to have anti-oxidative, anti-inflammatory and anti-proliferative effects. However, little it is known about its effects on mitochondrial morphology induced by hyperglycemia. The aim of the study is to demonstrate that H2S inhibits VSMC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 38 publications
0
29
0
Order By: Relevance
“…A previous study showed that H 2 S acting as a gasotransmitter can inhibit the proliferation of vascular smooth muscle cells [38][39][40]. Some research reported that SO 2 could inhibit the proliferation and migration of myocardial fibroblasts [41].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that H 2 S acting as a gasotransmitter can inhibit the proliferation of vascular smooth muscle cells [38][39][40]. Some research reported that SO 2 could inhibit the proliferation and migration of myocardial fibroblasts [41].…”
Section: Discussionmentioning
confidence: 99%
“…In this process, VSMCs make a transition from the contractile phenotype to a synthetic phenotype that allows vigorous cell proliferation and migration. Multiple studies have reported that NaHS inhibits VSMC proliferation and migration under the stimulation of serum, high levels of glucose, or homocysteine (43,160,177,205). Meanwhile, the apoptotic pathway is also activated in NaHS-treated VSMCs (190,191).…”
Section: Vascular Smooth Muscle Cell Functionmentioning
confidence: 99%
“…In an ex vivo study, high‐glucose treatment enhanced cell proliferation in human pulmonary arterial SMCs via increasing ROS generation (Sun et al . ), implying that pulmonary vascular resistance might be increased in diabetes. This will be discussed further in the ‘Hyperglycaemia and pulmonary hypertension’ section.…”
Section: Vascular Function In Hyperglycaemiamentioning
confidence: 99%